Identification of plant growth-promoting compounds in local isolated bacteria from chili plant root / Nur Zulaikha Mohamad Faudzi and Aslizah Mohd-Aris - Mohamad Faudzi, Nur Zulaikha; Mohd-Aris, Aslizah (Universiti Teknologi MARA, Sabah, 2023)
Plant Growth-Promoting Bacteria (PGPB) has been established as a cultivation strategy that manipulates biocontrol mechanisms within the agriculture industry. However, a detailed understanding of PGPB in the local setting is still somewhat understudied. This consequently limits the commercial value of PGPB. The objectives of this research converge towards identifying plant growth-promoting compounds and studying the growth of plants following a treatment using two potential PGPBs that were previously isolated from local chili plant roots (strains A4 and A8). Three elements were identified in this study; indole-3-acetic acid (IAA) production, phosphate solubilization, and biological nitrogen fixation (BNF). The ability to produce IAA was quantified using Salkowski's reagent. Additionally, the ability of both strains to grow on Pikovskaya's agar and yeast extract agar describes the capacity for phosphate solubilization and biological nitrogen fixation, respectively. The influence of both strains in promoting chili plant growth was assessed from a pot treatment. Essentially, it was found that both strains showed positive results in the compound detection analysis. Furthermore, the treatment using PGPB on chili plants showed an increase of 62.9 % in height and 57.1 % in number of leaves. In conclusion, A4 and A8 were strongly recommended for PGPB.